Negotiations on The Correct Direction of The Qibla: Had Al-A'la And Al-Adna Syahrur Against Radical Attitudes - Abd. Karim Faiz; Wahidin (Nizham Jurnal Studi Keislaman, 2026)
This approach aligns with Muhammad Syahrur’s Hudud concept, which emphasizes flexibility in sharia implementation. In contrast, FM2P views Qibla errors as serious violations that may invalidate prayers or even constitute apostasy. This study aims to explore: (1) the FM2P's view on errors in the direction of the Qibla and the attitudes of intolerance that accompany it, (2) the relevance of Muhammad Syahrur’s Hudud concept to Qibla errors and intolerance. The research method used is a qualitative approach with in-depth interviews, document analysis, and related literature reviews. The results of the study are; First, FM2P members view deviation from the Qibla direction as a serious error that can invalidate prayers, demanding absolute accuracy and judging those who reject the Qibla alignment as rejecting sharia. Second, analysis of the Al-Barkah Mosque and the Andalusia Mosque in Parepare shows that the azimuth of haad al-adna is approximately 292° 15′–292° 24′ and haad al-a'la refers directly to the Kaaba.